PENYELESAIAN PERMASALAHAN KREDIT TANPA AGUNAN (UMKM) DI DENPASAR - Arini, Ni Made; Wairocana, I Gusti Ngurah; Wiryawan, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 1 (2017)DO - 10.24843/AC.2017.v02.i01.p11, 2017)
Government of Denpasar city has a collaboration in distributing credit without agunan, namely Memorandum of Understanding (MOU) among Denpasar city government and PT, Bank Pembangunan Daerah Bali and PT. Asuransi Indonesia about micro small development, middle small development and cooperative with credit loan pattern No. Add: 893.3/1919/ORG.0182.107.2006.2, 17/MOU /LPKD/VII/2006 dated 26 th of July 2006, government of Denpasar city as a guarantor, however, the existance of Financial Investigation Agency based on governmental regulation of Indonesia Republic Number 54 of 2005, concerning Local Loan Article 4 point 1 that states “Regional Government is prohibited to assigne guarantee for other party loan”. Thus, there is a gap about contract agreement with Governmental Regulation of Indonesia Republic Number 54 of 2005 concerning Local Loan. In relations to this background, so the writer proposes 2 legal problems namely, How is the legal protection toward creditor if it takes place wanprestasi on credit without agunan to UMKM  in Denpasar and How is te effort done by bank in case there is a problem with credit without guarantee of UMKM in Denpasar. This type of study shows that in pursuant to Guarantee Legal Regulation and existing Banking Law, the requirement of guarantee in giving credit by bank is not an absolute prerequisite. If it takes place wanprestasi on credit without agunan UMKM in Denpasar so it will be under responsibility by PT. Askrindo as a guarantee. The effort done, in case, there is a problem of credit without a guarantee to UMKM in Denpasar, the settlement is done through Non Litigation, namely settlement in rescehduling, prerequsite again and manageable again.